Stress and common dermatological disorders: The psychophysiological dermatoses - Nupur Goyal; Smitha S Prabhu (Wolters Kluwer Medknow Publications, 2023)
Primary dermatological disorders which are frequently exacerbated by stress and whose course is affected by the psychological state of the patient are called psychophysiologic or psychosomatic diseases. Psychosocial stress plays a major role in the onset and/or aggravation of these skin diseases. A close relationship between the skin and the mind mediated via hormones and neurotransmitters and altered cutaneous permeability barrier homeostasis by psychological stress constitute the basic psychopathology. The common skin conditions precipitated/aggravated by stress include psoriasis, vitiligo, atopic dermatitis, acne vulgaris, alopecia areata, urticaria, lichen planus, prurigo, seborrheic dermatitis, and hyperhidrosis. These cutaneous diseases often have a chronic, unpredictable course with multiple remissions and relapses leading to significant psychiatric morbidity, and disease-related stress further acts as an aggravating factor for the cutaneous disease leading to a vicious cycle. Increased awareness about these psychophysiologic diseases among dermatologists has helped to incorporate psychotherapeutic treatment in the form of psychotropic drugs and nonpharmacological interventions in the management of these patients. A multidisciplinary approach consisting of dermatologists along with psychiatrists and psychologists in a liaison framework has proven useful for these patients.